Contaminants and Human Health Risks Associated with Exposure to Microplastic Ingestion of Green Mussels (Perna viridis) Collected from The Kedonganan Fish Market, Bali - Wiradana, Putu Angga; Sandhika, I Made Gde Sudyadnyana; Widhiantara, I Gede; Rizqy, Aimatun Nisfia; Soegianto, Agoes; Yulianto, Bambang (Jurnal Medik Veteriner, 2023)
Microplastics (MPs) are pollutant agents that have been absorbed and detected in aquatic ecosystems at high concentrations. This study aimed to investigate the presence of MPs pollution in green mussel (Perna viridis) products sold at the Kedonganan fish market, Badung, Bali. A total of 150 mussels with an average weight of 3,2 ± 0,71 g/mussels from three traders each composed and followed by the pre-treatment stage using 5 M NaCl solution, extraction with wet oxidation peroxidation (WPO) + Fe(II) catalyst and filtered. The highest percentage for the form of MPs was successively obtained by the Line form in Trader A at 85,42% and the lowest in Trader C at 50,00%. The highest form of fragments was obtained in Trader C at 42,86%. Film and filament forms were only obtained in Trader A. The highest MPs color was black and the lowest was gray. The highest average MPs particle size was found in the form of a filament of 1944,37 ± 88,41 Î¼m which was found in Trader A. Estimates of MPs intake per year/capita in Indonesia showed that exposure to MPs through consumption of green mussels in this study amounted to 498,330 MPs/year/capita items. Overall, the green mussel from Trader A had the highest percentage and size of MPs, with the shape of fragment MPs being dominated by Trader C and the color of the MPs being dominated by black. MPs exposure to green mussel consumption in Indonesia is very high, but no health impact category has yet been found for this estimate.